2013
DOI: 10.1159/000353096
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Dissolution of Calcium Oxalate Stones with Ethylenediaminetetraacetic Acid and Snake Venom Thrombin-Like Enzyme

Abstract: Objective: The aim of this study was to determine the feasibility of using snake venom thrombin-like enzyme (SVTLE) and/or ethylenediaminetetraacetic acid (EDTA) to dissolve calcium oxalate stones in vitro. Methods: Seven calcium oxalate stones were incubated with various chemolytic agents [EDTA, Tris-HCl/EDTA (TE) buffer or SVTLE diluted in TE buffer]. The pH, calcium concentration, stone weight and stone surface integrity were recorded, as well as related pathological changes to bladder mucosae. Results: Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Some findings suggested that chemical treatments may be useful for improving the efficacy of stone treatment via dissolving larger or harder stones. Zhou et al, 27 reported that buffered EDTA solvents might be feasible chemical treatment modalities for improving the efficacy of calcium oxalate stone dissolution.…”
Section: Results: Phytochemical Screening and Quantitative Estimation Of Phytoconstituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some findings suggested that chemical treatments may be useful for improving the efficacy of stone treatment via dissolving larger or harder stones. Zhou et al, 27 reported that buffered EDTA solvents might be feasible chemical treatment modalities for improving the efficacy of calcium oxalate stone dissolution.…”
Section: Results: Phytochemical Screening and Quantitative Estimation Of Phytoconstituentsmentioning
confidence: 99%
“…These phytoconstituents are of utmost significance for inhibiting urinary stone formation. Saponins possess antilithic properties and are known to disintegrate mucoproteins that are crucial components of the stone matrix 27 . Rutin, quercetin, hyperoside, and diosmin are known as flavonoids with high antioxidant and antilithiatic activities 28 .…”
Section: Results: Phytochemical Screening and Quantitative Estimation Of Phytoconstituentsmentioning
confidence: 99%
“…Some findings suggested that chemical treatments may be a useful for improving the efficacy of stone treatment via dissolving larger or harder stones. Zhou et al 30 reported that buffered EDTA solvents may be feasible chemical treatment modalities for improving the efficacy of CaOx stone dissolution. In present study, nBFMU was found active in dissolving the CaOX stones in concentration depended manner, which indicate that nBFMU contain some of the components that constitutes to increase the CaOX stone dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…Thousands of infected bladder stones were removed; stones weighed 612 g and the number of stones was about 1,500. Stone analysis showed that 70% was magnesium ammonium phosphate and 20% ammonium urate, rather than calcium oxalate, which is generally the most predominant (70-80%) type of urinary tract stone [1]. At 2 months of follow-up, the serum creatinine was 81 μmol/l and the hydronephrosis and hydroureter were significantly improved, while ultrasonic images showed that new stones could be observed in the bladder.…”
Section: Figmentioning
confidence: 99%